Sri Lanka : Staff Report for the 2014 Article IV Consultation and Second Post-Program Monitoring Discussion. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context. Macroeconomic performance has generally exceeded expectations. Real GDP grew 7.3 percent for 2013, up from 6.3 percent in 2012. Inflation declined to below 5 percent, and the external current account balance has improved. Private credit growth has been slow, however, a number of financial sector indicators have deteriorated. Outlook and Risks. Growth is expected to remain robust at 7 percent and inflation to remain in the mid-single digits. The external current account should improve marginally, allowing for further accumulation of foreign exchange reserves. Near-term risks appear moderate, although there may be some bumps in the road from market turbulence and climatic events. Medium-term risks relate to the potential for tighter external liquidity, the challenge of further fiscal and debt consolidation while maintaining high levels of investment in infrastructure and human capital, maintaining a balanced monetary policy, and staying competitive in a shifting economic landscape. Key Policy Recommendations. -- Fiscal consolidation and debt reduction need to continue, but the burden of adjustment needs to shift decisively to revenue generation. Debt targets could potentially be recast to achieve deeper reduction over a longer period. -- Monetary policy needs to maintain a balance between supporting growth and containing inflation. A continued forward-looking approach is needed given long lags in monetary transmission. -- Financial sector consolidation could lead to economies of scale, greater resilience, and more effective supervision, but corporate governance needs to continue to improve, and careful supervision in the post-consolidation period will be key. -- Maintaining competitiveness and achieving a more sustainable external position will require a mix of continued innovation, sustained investment in infrastructure and human capital, a predictable business environment, and ideally a heavier emphasis on direct investment and equity portfolio flows than debt.